MODY PDX1P33T: a mouse model reveals phenotypic divergence from human disease - Harten, Aliona; Schmidtke, Maximilian R.; Giesert, Florian; Skerrett-Byrne, David A.; Teperino, Raffaele; Przemeck, Gerhard K. H.; Hrabě de Angelis, Martin (Frontiers in Endocrinology, 2025)
IntroductionMaturity-onset Diabetes of the Young (MODY) is a rare form of diabetes and arises from mutations in key regulatory genes of the pancreatic beta cell, leading to their functional impairment and early-onset diabetes. Research into PDX1-MODY, a form of MODY caused by mutations in the PDX1 gene, enhances understanding of gene-specific mechanisms underlying glucose dysregulation and provides insights into possible approaches to restore normal metabolic function. However, no currently published mouse model accurately depicts the genetic cause of PDX1-MODY in human patients.MethodsUsing CRISPR-Cas9 technology, we generated the first mouse model carrying one of the most prevalent pathological PDX1 point mutation found in human patients, P33T, and conducted an 18-week in vivo phenotyping experiment assessing homozygous PDX1P33T and wild-type littermates on both chow and high fat diet (HFD). Additionally, transcriptomic and proteomic analyses were performed on isolated pancreatic islets. Islet architecture was investigated via fluorescent microscopy.ResultContrary to expectations, our comprehensive phenotypic analysis of the mouse model carrying the homozygous PDX1P33T mutation revealed no significant differences in metabolic parameters compared to wild-type controls, and no pathological outcomes were observed as seen in human patients. Notably, male PDX1P33T mice exhibited an increase in islet size and number on chow diet, with omics analyses suggesting reprogramming toward stress resilience, but failed to adapt respectively on HFD.DiscussionOur work indicates substantial differences between mouse and human PDX1 function in the pancreas. Further refinement of animal models is necessary to better elucidate the pathophysiology of PDX1-MODY.